Transgresión a la Ley de Cheques por la emisión del cheque pos datado. - Mora Díaz, Eduardo Vicente (2011)
The Check as a legal instrument of purchase and payments in the different fields of commerce has its main action and benefit which is manifested by the fact that people do not carry cash. From very old times, the merchants saw the need to have an instrument that allows them to face their commercial needs and at the same time make continuity in the different businesses that were carried out. However, its use has not been perfected legally, which is why it is necessary to deepen in juridically regulating important aspects about utilization, payments and issuance of post dated checks that are the ones with the highest circulation. The law of check penalizes those who issue post dated checks with fines, however this is the document that is most commonly used commercially in the exchange of goods and services. The commercial advantages are many and the merchants who use this instrument see in it better investment opportunities.